2018
DOI: 10.1111/mec.14765
|View full text |Cite
|
Sign up to set email alerts
|

Habitat loss and fragmentation reduce effective gene flow by disrupting seed dispersal in a neotropical palm

Abstract: Habitat loss and fragmentation often reduce gene flow and genetic diversity in plants by disrupting the movement of pollen and seed. However, direct comparisons of the contributions of pollen vs. seed dispersal to genetic variation in fragmented landscapes are lacking. To address this knowledge gap, we partitioned the genetic diversity contributed by male gametes from pollen sources and female gametes from seed sources within established seedlings of the palm Oenocarpus bataua in forest fragments and continuou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 95 publications
(167 reference statements)
3
44
1
Order By: Relevance
“…This might also have important conservation implications, as some key frugivores (e.g., umbrellabirds) in the O. bataua system are directly threatened by hunting, habitat degradation and habitat loss whereas others (e.g., toucans) appear to be more resilient (Walter et al., ). For example, in a companion paper we show evidence for a stronger impact of forest loss and fragmentation on seed dispersal than pollen flow for O. bataua , consistent with shifts in the relative contribution of different foraging ecologies to the dispersal and genetic structure of O. bataua (Browne & Karubian, ). In closing, we suggest future studies would benefit from considering both dispersal distance and effective number of sources at deposition sites (as opposed to dispersal distance alone) when attempting to characterize how seed dispersal may impact genetic diversity and fine‐scale spatial genetic structure.…”
Section: Discussionsupporting
confidence: 70%
“…This might also have important conservation implications, as some key frugivores (e.g., umbrellabirds) in the O. bataua system are directly threatened by hunting, habitat degradation and habitat loss whereas others (e.g., toucans) appear to be more resilient (Walter et al., ). For example, in a companion paper we show evidence for a stronger impact of forest loss and fragmentation on seed dispersal than pollen flow for O. bataua , consistent with shifts in the relative contribution of different foraging ecologies to the dispersal and genetic structure of O. bataua (Browne & Karubian, ). In closing, we suggest future studies would benefit from considering both dispersal distance and effective number of sources at deposition sites (as opposed to dispersal distance alone) when attempting to characterize how seed dispersal may impact genetic diversity and fine‐scale spatial genetic structure.…”
Section: Discussionsupporting
confidence: 70%
“…A lack of significant genetic structure at both cpDNA and mtDNA was confirmed by BAPS analysis applied to natural and transplanted population (Figure 2 ). These results suggest that extensive gene flow might compensate the barrier of genetic change in mountainous terrain ( Austerlitz et al, 2004 ; Hu et al, 2008 ; Browne and Karubian, 2018 ). However, retention of ancestral alleles is an alternative explanation as species with a long life span and a large effective population size tend to preserve these alleles.…”
Section: Discussionmentioning
confidence: 86%
“…When genetic structure between genomic compartments was translated into a pollen/seed flow ratio (m p /m s = 2) it revealed that pollen flow is two times more efficient than seed dispersal. Although in orchids and other plants pollen flow may be a strong cohesive force (Pinheiro et al 2014;Browne and Karubian 2018), in C. calceolus, due to small (rarely longer than 600 m) foraging distance of its putative pollinators (Gathmann and Tscharntke 2002;Zurbuchen et al 2010), the homogenizing influence of pollen flow on populations' genetic diversity may be expected only over short distances. Effective seed dispersal distances were even lower in the studied species and did not exceed 5 m (Brzosko et al 2017b).…”
Section: Population Genetic Structure and Gene Flow In A Fragmented Lmentioning
confidence: 99%